Assessment of the sustainability of family farmers agroecosystems in the watershed of Cormechoque river (Boyaca — Colombia) - Fonseca-Carreño, Jorge Armando; Cleves-Leguízamo, José Alejandro; León-Sicard, Tomás (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The research determines the sustainability level of farmers families agroecosystems in the watersheds of river Cormechoque in Boyaca (Colombia). The objective was to analyze and evaluate peasant agricultural practices and their effect on the productive, environmental and financial performance of such agroecosystems, The "Frameworl for assessing management systems of natural resources incorporating sustainability indicators" (MESMIS) was utilized from the biotic, technological and socio-economic components characterization, through six evaluation criteria and fifteen sustainability indicators, rated on a scale from 1 to 5.The results show that there are differences between the biological composition, technological and socioeconomic aspects in agroecosystems evaluated, due to differences in agricultural practices and management of environmental supply. The Tocavita agroecosystem had the highest level of sustainability due to the indicators group performance that account for the management of environmental supply (availability of water, biodiversity, soil quality), as well as cultural practices (plant cover, use of local seeds, training and dependence on external inputs) that positively impacts the profitability indicators group (Net present value and cost benefit) resulting in greater permanence of the family unit in agricultural activities.